2000
DOI: 10.1046/j.1523-5408.2000.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Warfare: The Role of Short‐Chain Fructooligosaccharides in Health and Disease

Abstract: Short‐chain fructooligosaccharides (FOS) are a long‐studied functional food made up of a glucose molecule linked to between 2 and 4 fructose molecules and not significantly digested in the small intestine. Short‐chain FOS provide an energy source that is relatively specific for beneficial bacteria in the large intestine, with even small amounts leading to dramatic increases in bifidobacteria, which have a variety of health benefits in and of themselves. In addition, a predicable fall in pathogenic bacteria, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…When FOS is fermented in the large intestine, short-chain fatty acid concentrations such as butyrate increase within the colonic lumen [32,33]. Butyrate is a major source of energy for colonocytes to grow and proliferate, and it has been suggested that a defective butyrate metabolism may be involved in the pathogenesis of human ulcerative colitis [24,34].…”
Section: Discussionmentioning
confidence: 99%
“…When FOS is fermented in the large intestine, short-chain fatty acid concentrations such as butyrate increase within the colonic lumen [32,33]. Butyrate is a major source of energy for colonocytes to grow and proliferate, and it has been suggested that a defective butyrate metabolism may be involved in the pathogenesis of human ulcerative colitis [24,34].…”
Section: Discussionmentioning
confidence: 99%
“…18 In studies of humans with IBD or colitis, adding FOS to the diet highly improved the response to therapy, clinical disease was reduced, and relapses were fewer. 19 There have been only a few studies in dogs, and even fewer in cats, evaluating the role of FOS in the dietary therapy of GI disease. However, preliminary evidence supports the finding in humans that FOS increases the numbers of beneficial bacteria in the colon of dogs and cats, and may prove beneficial in controlling bacterial overgrowth, antibiotic responsive diarrhea, or other inflammatory diseases suspected to have a bacterial origin (eg, IBD).…”
Section: Chomentioning
confidence: 99%
“…They proceed undigested and unresorbed through the upper part of the gastrointestinal tract. Once in the colon, FOS are rapidly fermented to short-chain fatty acids, especially by Bifidobacteria, whose growth is consequently promoted (100). The breakdown of FOS by bacterial fermentation is followed by a pronounced increase in hydrogen concentrations, which promotes peristalsis of the colon and can be responsible for side effects like bloating, flatus, abdominal rumbling, and an irregular defecation pattern (109).…”
Section: Prebioticsmentioning
confidence: 99%